Physico–mechanical properties of Sesenduk at 12% initial moisture content treated with direct contact heat treatment method - Mohd Fauzi, Muhamad Faiz (2017)
Under-utilized species such as Sesenduk have a high potential to be an alternative to substitute wood as a raw material. This study describes the effects of thermal modification with direct contact of heat treatment method on physical and mechanical properties of Sesenduk wood at different level of thickness, temperature and time. Samples of Sesenduk wood (80mm x 320mm) with the thickness of 1cm, 1.5cm and 2cm were heat-treated at 1600C, 1800C and 2000C with 15 minutes, 30 minutes and 45 minutes. The physical properties were determined by water absorption and volumetric swelling tests. The mechanical properties were determined by 3 points static bending tests. The result showed that the thickness and the level of temperature affected significantly on water absorption and volumetric swelling while the length of exposure did not influence the physical properties. The values for MOR had significantly affected by the different level of temperature and the values of MOE had significantly affected by thickness and duration of time. The visual color changes were more distinct after heat treatment above 1800C and the time of 45 minutes. Temperature had a greater influence than time on these properties of samples.